Does dual employment protection affect TFP? Evidence from Spanish manufacturing firms - Juan J. Dolado; Salvador Ortigueira; Rodolfo Stucchi (SERIEs - Journal of the Spanish Economic Association, 2016)
This paper analyzes how changes in the firing-costs gap between permanent and temporary workers affect firms' TFP in a dual labour market. We argue that, under plausible conditions, firms' temp-to-perm conversion rates go down when this gap increases. Temporary workers respond to lower conversion rates by exerting less effort, while firms react by providing less paid-for training. Both channels lead to a decline in TFP. We test these implications in a large panel of Spanish manufacturing firms from 1991 to 2005, looking at the effects of three labour market reforms which entailed substantial changes in the firing-costs gap. Our empirical findings provide some support for the above-mentioned mechanism.
Keywords: C14; C52; D24; J24; J41; 330; Firms' TFP; Workers' effort; Training; Temporary contracts; Firing costs